ENGLISH PHONETICS - Nurhayati, Dwi Astuti Wahyu (Research Collections, 2013)
This English Phonetics Dictate in the form of Â summary and completed with exercises is designed for students of the English Department, Faculty of Tarbiyah, State College For Is- lamic Studies Tulungagung.It is a six-month course, and it is hoped, may help the stu-dents to improve their speech as well as the future teachers to correct their studentsâ mistake in pronouncing English, so that in the next or future they will be able Â to practice, pronounce their English correctly.As English phonetics covers the production, transmission, and reception of speech sounds, this book only discuss the study of the production of speech sounds.It is based on Daniel Jonesâ An Outline of English Phonet- icsâ as standard English Pronunciation and some American En- glish intonation Â added by Kelly materials. The terminology is based on Jonesâ book. The Materials are also taken partly from: Ann Baker, Gerald Kelly, A. Kusuma, Marianne Celce Murcia: all of them are professors of Phonetics, and partly from other references like website.My sincere thanks are due to all of them mentioned above. I gratefully acknowledge my indebtedness to my lectures, among others Mr. A.Kusuma, Wisasaongko,Soekamto, Univer-sity of Jember.